A Novel Filtering Power Divider Based on Ring Resonator - Yong Xia; Feng Wei; Xiaowei Shi (International Journal of Antennas and Propagation)
In this paper, a compact dual-band filtering power divider (FPD) combined by conventional Wilkinson power divider and dual-mode resonators is proposed. The resonators submitting the quarter wavelength transmission line can act as a filter. The proposed resonator is composed of two cascading symmetrical ring branches connected to the ground in the middle. The inter-digital coupling structure constitutes the feed lines of the band-pass filter (BPF) operating at 2.45/5.8 G. The resonator with symmetrical structure is analyzed by the odd-even mode method in detail. The two resonant frequencies can be adjusted by the length of the stub separately. In addition, two isolation resistors are placed at proper position for ensuring the isolation effect. The proposed FPD is fabricated for verifying simulation results, and good agreements between the simulated and measured results are achieved here.